Performance and emission characteristics of a diesel engine operating with biodiesel - Muhammad Shukri, Rabain (2010)
The use of biodiesel as an alternative diesel engine fuel is increasing rapidly. However, due to technical deficiencies, they are rarely used purely or with high percentages in unmodified diesel engines. Therefore, in this study, biodiesel is used as alternative fuel in a diesel engine. The tests were conducted on a typical four-stroke, four cylinders, water-cooled, direct-injection diesel engine. The effect of test fuels on engine torque, power, brake specific fuel consumption, brake mean effective pressure, and CO, CO2, NOx and HC emissions was investigated. The experimental results showed that the performance of diesel engine was improved with the use of the biodiesel compared to diesel fuel. Besides, the exhaust emissions for biodiesel were fairly reduced.